x(2x-2)+x(2x-4)=(4x+7)(x-3)

Simple and best practice solution for x(2x-2)+x(2x-4)=(4x+7)(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(2x-2)+x(2x-4)=(4x+7)(x-3) equation:


Simplifying
x(2x + -2) + x(2x + -4) = (4x + 7)(x + -3)

Reorder the terms:
x(-2 + 2x) + x(2x + -4) = (4x + 7)(x + -3)
(-2 * x + 2x * x) + x(2x + -4) = (4x + 7)(x + -3)
(-2x + 2x2) + x(2x + -4) = (4x + 7)(x + -3)

Reorder the terms:
-2x + 2x2 + x(-4 + 2x) = (4x + 7)(x + -3)
-2x + 2x2 + (-4 * x + 2x * x) = (4x + 7)(x + -3)
-2x + 2x2 + (-4x + 2x2) = (4x + 7)(x + -3)

Reorder the terms:
-2x + -4x + 2x2 + 2x2 = (4x + 7)(x + -3)

Combine like terms: -2x + -4x = -6x
-6x + 2x2 + 2x2 = (4x + 7)(x + -3)

Combine like terms: 2x2 + 2x2 = 4x2
-6x + 4x2 = (4x + 7)(x + -3)

Reorder the terms:
-6x + 4x2 = (7 + 4x)(x + -3)

Reorder the terms:
-6x + 4x2 = (7 + 4x)(-3 + x)

Multiply (7 + 4x) * (-3 + x)
-6x + 4x2 = (7(-3 + x) + 4x * (-3 + x))
-6x + 4x2 = ((-3 * 7 + x * 7) + 4x * (-3 + x))
-6x + 4x2 = ((-21 + 7x) + 4x * (-3 + x))
-6x + 4x2 = (-21 + 7x + (-3 * 4x + x * 4x))
-6x + 4x2 = (-21 + 7x + (-12x + 4x2))

Combine like terms: 7x + -12x = -5x
-6x + 4x2 = (-21 + -5x + 4x2)

Add '-4x2' to each side of the equation.
-6x + 4x2 + -4x2 = -21 + -5x + 4x2 + -4x2

Combine like terms: 4x2 + -4x2 = 0
-6x + 0 = -21 + -5x + 4x2 + -4x2
-6x = -21 + -5x + 4x2 + -4x2

Combine like terms: 4x2 + -4x2 = 0
-6x = -21 + -5x + 0
-6x = -21 + -5x

Solving
-6x = -21 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-6x + 5x = -21 + -5x + 5x

Combine like terms: -6x + 5x = -1x
-1x = -21 + -5x + 5x

Combine like terms: -5x + 5x = 0
-1x = -21 + 0
-1x = -21

Divide each side by '-1'.
x = 21

Simplifying
x = 21

See similar equations:

| (2x^4+7x^3-8)-(7x^2-5x+4)= | | -2-5x=-2(1+4x) | | 1/2*b*19.8 | | 7g+8=22 | | 0.2x=-0.7 | | R=1-2n+5 | | 4x+4x+3=0 | | 14-12=x/-4 | | 5x/4-3=7x/6 | | 17-3(4-3x)=6x-1 | | (-2z/y^3)^2 | | 1/3(m-3n)=2 | | 3x(-5)/2x | | 0.55=logx | | -4-p=8p-5(6+7p) | | (3xy^2-2y)=0 | | f(2e^4)=lnx | | 2=4-2f | | 81/54 | | 10x-20=-5x+10 | | -15=-k-4k | | x-.15x=7849.08 | | 4a^2-6a^6/8a^-3 | | x+6+3x=-18 | | 6-14=z/-4 | | 30+.5x=1.25x | | x+(-7)=-77 | | x-.15x=4812.96 | | 4.25z=4.5z-6.25+6.25 | | x^2+4x+8y+1=0 | | x^2+10x+y+20=0 | | -3b+9=15 |

Equations solver categories